Islamic Character Enhancement through Intensive Coaching Programme for Tahfiz Darul Falah Selangor Students: An Indonesia-Malaysia Collaboration - Moch. Sya'roni Hasan; Qurrotul Ainiyah; Muhammad Anas Ma`arif; Zahrotun Ni’mah Afif; Julianne Kamelia Riza; Qorriatul Ikrima (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2025)
This community service activity aims to strengthen the Islamic character of tahfiz students through an intensive guidance programme based on Indonesia-Malaysia collaboration in Darul Falah Selangor. Islamic character education is a fundamental foundation in shaping a generation of quality huffaz, yet the challenge of integrating Quranic values into daily behaviour remains a major issue. This community service programme used a participatory action research approach involving 45 tahfiz students for six months. The implementation method included three stages: preparation with needs assessment, implementation of an intensive mentorship programme for four months, and ongoing evaluation. Results showed significant improvements on three dimensions of Islamic character: akhlaq towards Allah (89% increase in sunnah worship and 82% in recitation quality), akhlaq towards fellow humans (78% decrease in conflict and 85% increase in communication skills), and akhlaq towards the environment through the green pesantren initiative. The programme succeeded in increasing motivation to memorise by 91% with a 65% decrease in recitation errors and a 78% increase in memorisation fluency. An Indonesia-Malaysia collaboration resulted in an innovative mentoring model that combines local pesantren wisdom with modern technology. This programme proved to be effective in producing a generation of huffaz who excel in memorisation while having a strong Islamic character.